BENCHMARKING PROGRESS ON CHILD SAFETY ACTION IN EUROPE—THE RESULTS OF THE 2012 CHILD SAFETY REPORT CARDS. (7th October 2012) - Mackay, M; Vincenten, J; Lyons, RA; Macey, S; Turner, S
Abstract : Background: Despite the existence of effective measures to reduce child unintentional injury, they are not always adopted and implemented. A lot of what is known to work requires government action in the form of national level policy or legislation. Child Safety Report Cards, developed in Europe in 2005, identify policy gaps, allow general European-level comparisons and measurement of improvements over time. Aims/Objectives/Purpose: To measure uptake and implementation of national level policies to support child injury prevention in 31 European countries in 2012 and progress over 5 years. Methods: Data for 115 policy indicators addressing unintentional child injury were obtained using English language survey tools. Issue specific and overall scores were calculated. Trend analyses to compare scores in 2007, 2009 and 2012 were conducted using paired t-tests. Results/Outcome: None of the countries have adopted and implemented all recommended policies. Uptake is highest for road safety, while uptake of those related to home safety is lower. Between 2007 and 2012 the change in overall score for the 16 countries participating in both time periods ranged from −6.5 to +18.5 with the greatest improvements occurring in fall prevention, burn/scald prevention, pedestrian safety and leadership, and in countries where investments have been made in the last 5 years (eg, Czech Republic, Hungary, Scotland and Spain). The average increase of 5.09 was statistically significant (p=0.019; 95% CI 0.96 to 9.22). Significance/Contribution to the field: While a crude measurement tool, the Child Safety Report cards have become an accepted benchmarking tool and have proved to be an effective advocacy tool driving action toward evidence-based good practices.